The Influence of Lean Supply Chain, Information Technology and Socially Oriented Sustainability on Operational Performance in Panel Manufacturing Companies - Rangga Farras AL Sajid; Dadang Surjasa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study of panel manufacturing firms examines lean supply chains, information technology, and socially-oriented sustainability. Just-in-time statistical process control and lead time reduction have three dimensions in this study of thin supply chains. Big data, cloud computing, and the internet of things focus on this study's information technology dimensions. Safety and health, employee well-being, and product responsibility are all socially-oriented sustainability variables that can be measured. The primary data used in this study comes from the distribution of questionnaires to 4-panel manufacturing company employees. The purposive sampling method was used to select the research sample, resulting in 185 models from four-panel manufacturing companies. It is used for hypothesis testing in the form of SEM using IBM AMOS 24 software and IBM SPPS 22. Research shows that lean supply chains positively impact social sustainability and operational effectiveness. Data shows that IT can directly affect social sustainability and operational performance. A positive correlation was found between operational efficiency and socially conscious sustainability. The results of this study provide information that applying a lean supply chain and information technology can improve socially oriented sustainability and the company's operating performance, which will later create sustainability performance that can benefit all parties, both within the company and the community around the company.